Determination of the worst case for cleaning validation of equipment used in the radiopharmaceutical production of lyophilized reagents for 99mTc labeling - Luciana Valéria Ferrari Machado Porto; Neuza Taeko Okasaki Fukumori; Margareth Mie Nakamura Matsuda
ABSTRACT Cleaning validation, a requirement of the current Good Manufacturing Practices (cGMP) for Drugs, consists of documented evidence that cleaning procedures are capable of removing residues to predetermined acceptance levels. This report describes a strategy for the selection of the worst case product for the production of lyophilized reagents (LRs) for labeling with 99mTc from the Instituto de Pesquisas Energéticas e Nucleares (IPEN-CNEN/São Paulo). The strategy is based on the calculation of a "worst case index" that incorporates information about drug solubility, cleaning difficulty, and occupancy rate in the production line. It allowed a reduction in the required number of validations considering the possible manufacturing flow of a given product and the subsequent flow, thus facilitating the process by reducing operation time and cost. The products identified as "worst case" were LRs PUL-TEC and MIBI-TEC.